Organic Manure Improves Soybean Response to Rhizobia Inoculant and P-Fertilizer in Northern Ghana - ULZEN, Jacob; Abaidoo, Robert C.; Ewusi-Mensah, Nana; Osei, Ophelia; Masso, Cargele; Opoku, Andrews (Frontiers in Agronomy, 2020)
Inherently low concentrations of soil nutrients and erratic rainfall pattern in sub-Sahara Africa limit soybean response to rhizobia inoculant and P-fertilizer. The study was conducted to: (i) improve soybean response to rhizobia inoculation and P-fertilizer through the addition of organic manure; (ii) enhance rain water use efficiency and (iii) determine the economic viability of combined application of the three factors in soybean cropping systems in the Northern region of Ghana. A factorial experiment with two levels of rhizobia inoculant, two levels of Phosphorus, two different kinds organic manure (fertisoil (a commercially prepared compost from urban waste, rice husks, poultry manure and shea butter waste) and cattle manure) and a control arranged in randomized complete block design with three replications was established on farmers’ fields. The combined application of rhizobia inoculant, P-fertilizer and organic manure markedly increased nodulation, shoot biomass, haulms, harvest index (HI), P agronomic efficiency (P-AE) and rain water use efficiency (RUE) compared to the control. The combined application of rhizobia inoculant, P-fertilizer and fertisoil increased grain yield by four-folds whereas the combined application of rhizobia inoculant, P-fertilizer and cattle manure increased grain yield by three- folds. Harvest index, P-AE and RUE were relatively higher with the fertisoil treatment combinations than with the cattle manure combinations and the control treatment. The application of rhizobia inoculant, P-fertilizer in combination with fertisoil was profitable with VCR of 2 as compared to the combination of cattle manure which had a VCR of 0.40. The results showed that fertisoil offers a better option of improving soybean response to rhizobia inoculant and P-fertilizer; and has the potential to enhance rain water use efficiency. However, the long term benefit must be quantified.